Effect of the support systems' compliance on total hip modular taper seating stability. (September 2018) - Scholl, Laura; Pierre, David; Rajaravivarma, Raga; Lee, Reginald; Faizan, Ahmad; Swaminathan, Viswanathan; TenHuisen, Kevor; Gilbert, Jeremy L; Nevelos, Jim
Assembly of a femoral head onto the stem remains non-standardized. The literature shows altering mechanical conditions during seating affects taper strength and lower assembly load may increase fretting corrosion during cyclic tests. This suggests overall performance may be affected by head assembly method. The purpose of this test was to perform bench-top studies to determine influence of peak force magnitude, load rate, and compliance of the system's support structure on initial stability of the taper. Custom manufactured CoCrMo femoral heads and Ti-6Al-4V taper analog samples were assembled with varying peak force magnitudes (2–10.1 kN), load rates (quasi-static vs impaction), and system compliance (rigid vs compliant). A clinically-relevant system compliance design was based off of force data collected during a cadaver impaction study. Tensile loads were then applied to disassemble the taper and quantify initial taper stability. Results indicated that taper stability (assessed by disassembly forces) increased linearly with assembly force and load rate did not have a significant effect on taper stability. When considering system compliance, a 42%–50% larger input energy, dependent on assembly force, was required in the compliant group to achieve a comparable impaction force to the rigid group. Even when this impaction force was achieved, the correlation between the coefficient, defined as distraction force divided by assembly load, was significantly reduced for the compliant test group. The compliant setup was intended to simulate a surgical scenario where patient and surgical factors may influence the resulting compliance. Based on results, surgical procedure and patient variables may have a significant effect on initial taper stability.